2018
DOI: 10.1111/andr.12494
|View full text |Cite
|
Sign up to set email alerts
|

Associations between circulating sex steroid hormones and leukocyte telomere length in men in the National Health and Nutrition Examination Survey

Abstract: Preliminary evidence suggests that sex steroid hormones, such as danazol (a synthetic sex steroid hormone), may be involved in enhancing telomerase activity. Elucidating underlying mechanisms of telomerase activity may further therapeutic options for individuals with telomeropathies and potentially avert certain age-related conditions. Therefore, we conducted a cross-sectional study to investigate the relationship between circulating sex steroid hormones and SHBG with leukocyte telomere length among 499 males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
7
1
1
Order By: Relevance
“…These findings are in contrast to previous reports (see Table ) which reported neutral or inverse associations of E2 with LTL in men . In the study by Bekaert of 110 men with median age 75.0 years, circulating T and E2 were measured using immunoassay, bioavailable (non‐SHBG bound) T and E2 were calculated, and LTL was assayed using Southern blots.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…These findings are in contrast to previous reports (see Table ) which reported neutral or inverse associations of E2 with LTL in men . In the study by Bekaert of 110 men with median age 75.0 years, circulating T and E2 were measured using immunoassay, bioavailable (non‐SHBG bound) T and E2 were calculated, and LTL was assayed using Southern blots.…”
Section: Discussioncontrasting
confidence: 76%
“…Neither calculated bioavailable T nor E2 correlated with LTL . Coburn studied 499 men from NHANES 1992‐2002 surveys with median age 42.0 years, with circulating T and E2 concentrations assayed using immunoassays and LTL measured using PCR. In that study, circulating T was not associated with LTL, whereas circulating E2 was inversely associated with LTL in analyses adjusting for age, ethnicity, education, BMI and smoking status .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary evidence suggests that sex steroid hormones could be involved in enhancing telomerase activity since serum dihydrotestosterone and estradiol are positively correlated with leukocyte TL independently of age (Yeap et al, 2016(Yeap et al, , 2020. However, other studies have demonstrated no association of short TL with sex hormones in healthy men and women (Coburn et al, 2018;Gu et al, 2020).…”
Section: Telomere-related Senescence Mechanismsmentioning
confidence: 99%
“…Esperava-se também uma relação negativa com qualquer situação estressora de vida, como já observado em diferentes estudos. O encurtamento do telômero tem sido mais acelerado em mulheres do que em homens e sua preservação não se associa a hormônios esteróides masculinos (Coburn et al, 2018).…”
Section: Análiseunclassified